PERBANDINGAN MINAT KELAS IPA DAN KELAS IPS TERHADAP PEMBELAJARAN PENDIDIKAN JASMANI, OLAHRAGA, DAN KESEHATAN DI SMA - FEBRI RAHMAWAN, EKO (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract In the world of senior high school education (high school) there are two different majors natural sciences (IPA) and social science (IPS). Both majors have the characteristics of students and academic learning are different, those differences impact the students' interest in learning of sport and physical education, interest will either give a good impact on the learning objectives.The goal of such research was to get information about students' interest towards the learning of sport and physical education in SMAN 1 Sidoarjo. Researchers in this study used a quantitative approach to the type non-experimental research design was survey and comparability. The variable in this study is the difference in grade science and social studies classes (independent variable) and an interest in teaching physical education, sport, and health (dependent variable). The population in this study were all students of class XI and XII in SMAN 1 Sidoarjo and the samples of the research were three classes of science class, a class XI IPA 5, XI IPA 8, and 4 and class XII science XI IPS 1, XI IPS 2, XII IPS 1, and XII IPS 2.The results of the analysis of students' interest in science classes and social studies classes to learning of sport and  physical education in SMAN 1 Sidoarjo was no significant difference can be seen from the results of  thitung 1.249  declared value is not significant at the 5% level of accuracy because the sig (2-tailed) in the calculation of 0.214 > more than the value of alpha (a = 0.05). Interests grade science and social studies classes to teaching physical education, sport, and health fall into the category that the show was the percentage of IPA by 63 , 8% and 62.7% grade social studies. thus concluded that free no difference between interest-class science and social studies classes at SMAN 1 Sidoarjo Keywords : Interest of student class IPS and class IPS, learning of sport and physical education